(untitled) (Konferensiyalar | Conferences, 2024)
This article explores the landscape of innovative pedagogical technologies in education, highlighting various tools and methods that enhance teaching and learning experiences. It discusses the benefits of integrating technologies such as virtual reality, gamification, adaptive learning systems, artificial intelligence, and mobile learning apps into educational practices.